A Qualitative Study of Project-Based Learning Implementation in Urban Farming Activities for Children Aged 5-6 Years - Endah Sri Lestari; Kartika Fajriani; Lina Revilla Malik (Kumara Cendekia, 2026)
Activity urban farming is a project-based learning approach that can foster character and active involvement in early childhood through real-life experiences in the surrounding environment. The purpose of this study is to explain how the project-based learning (PjBL) model is implemented and to understand the role of teachers in these activities urban farming conducted by children aged five to six years. This study used a qualitative methodology and was designed as a case study. Data were collected through interviews with the principal and teachers, as well as observing students during activities. Data were analyzed using interactive analysis techniques through data reduction, data presentation, and drawing conclusions. The results of the study indicate that three main stages, namely planning, implementation, and assessment, are used to implement PjBLThe results indicate that teachers do not fully understand all stages of PjBL, especially the stages of child care and reflection. Therefore, training and mentoring are needed for teachers so that PjBL implementation can take place more systematically and optimally.